TAX PLANNING IN THE FINANCIAL MANAGEMENT SYSTEM - POHRISHCHUK, Halyna; HOLOVAI, Nadiia; BEI, Snizhana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines in detail the importance of tax planning at the micro level. The main focus is on the analysis of the concept of tax planning, as well as a comprehensive study of the tactics and tools used in tax planning.It has been established that the tax strategy of the enterprise in the modern paradigm should be determined not only by calculating tax liabilities, but also by carefully studying the possibilities of their optimization. It has been proven that the effective use of tax incentives and the ability to avoid excessive tax burdens make it possible to significantly improve the financial position of business entities.One of the most common methods of reducing the tax burden is strategically oriented tax planning. There are other methods of tax optimization, but not all of them are legally acceptable. In the context of domestic law-making, where tax laws are often contradictory and interpretations can vary, the line between legal and illegal methods of taxation can be blurred and ambiguous. Under such conditions, it is important to clearly distinguish between concepts such as tax evasion, tax avoidance and legitimate tax planning.The tax planning process involves close cooperation between the manager, the accounting (financial) service and the lawyer. These specialists work on the development of appropriate innovative approaches and strategies, which include a thorough study of legislation, specialized literature, and also study successful practices in the field of taxation of other enterprises and organizations.Effective tax planning, involving the involvement of qualified specialists in this field, careful compliance with current legislation, systematic consultations with fiscal authorities and maximum optimization of the tax burden, is a key factor in creating a highly profitable, legitimate and stable business. These measures not only increase the financial efficiency of the enterprise, but also ensure compliance of its activities with legal requirements, thereby strengthening its position on the market.
Keywords: essence of tax planning; differences of tax planning; tax planning methodology; tools for measures during tax planning